Properties and applications of biochars derived from different biomass feedstock sources - Xiaofeng, Bai; Xiaoqin, Zhou; Zifu, Li; Jiewen, Ni; Xue, Bai (International Journal of Agricultural and Biological Engineering, 2017)
In China, substantial agricultural and garden wastes are burned yearly. This practice not only wastes resources but also pollutes air. Corn straw and poplar leaves are typical agricultural and garden waste in China. In this study, corn straw and poplar leaves were used to prepare biochars with different pyrolysis temperatures (250°C, 350°C, 450°C, 550°C and 650°C) and were labeled as CC (corn straw) and LC (poplar leaves), respectively. The biochars were characterized through elemental analysis, Brunauer-Emmett-Teller surface area analysis, scanning electron microscopy and Fourier transform infrared spectroscopy. Yield, ash content and biochar pH were also measured. Results showed that the two biochars possessed some similar characteristics with increasing pyrolysis temperature. These attributes included increased carbon content, biochar hydrophobicity, alkaline pH; decreased hydrogen and oxygen contents and polar functional group content; and enlarged surface area. The biochars also displayed some different characteristics, such as the obviously larger surface area of CC than that of LC at high pyrolysis temperatures and the regular holes of CC and irregular and disordered holes of LC. When biochars CC-650 and LC-650 were used as soil conditioners, the soil pH increased by 0.3 and 0.4 units, respectively, and the soil cation exchange capacity increased by 12.7% and 21.5%, respectively, with respect to those of the blank controls.Keywords: biochars, corn straw, poplar leaves, pyrolysis, thermochemical propertyDOI: 10.3965/j.ijabe.20171002.2878Citation: Bai X F, Zhou X Q, Li Z F, Ni J W, Bai X. Properties and applications of biochars derived from different biomass feedstock sources. Int J Agric & Biol Eng, 2017; 10(2): 242–250.